Hybrid three-stage repair of mega aorta syndrome with the Lupiae technique - Troisi, Nicola; Bichi, Samuele; Patrini, Davide; Arena, Vincenzo; Setti, Marco; Pitì, Antonino; Esposito, Giampiero (The Journal of thoracic and cardiovascular surgery, 2013)
Open surgical replacement of the whole aorta in mega aorta syndrome remains a surgical challenge. We report our experience in the treatment of patients with mega aorta syndrome using a 3-stage hybrid repair. From January 2006 to December 2011, 12 patients with mega aorta syndrome underwent total replacement of the aorta with a 3-stage hybrid repair, consisting of total replacement of the arch (first stage), retrograde revascularization of the visceral vessels (second stage), and deployment of an endograft (third stage). The intraoperative, early (30-day), and follow-up results were analyzed. No intraoperative mortality occurred in any of the open or endovascular procedures. After the first stage, 1 patient died, resulting in a 30-day mortality of 8.3%. After the second stage, the overall major morbidity was 27.3% (1 surgical revision and 2 temporary dialysis treatments). After the third stage, no conversion or major complication was recorded. The overall mean follow-up period was 31.9 months (range, 1-60 months). One patient died at 10 months postoperatively, and another patient required adjunctive implantation of a stent graft for a type III endoleak. At 3 years, the estimated survival, freedom from any device-related reinterventions, and freedom from type I endoleak was 83.3%, 77.9%, and 100%, respectively. Our hybrid 3-stage approach seems to be effective in the treatment of mega aorta syndrome. The second stage was affected by non-negligible rates of perioperative complications. The overall mid-term results were encouraging, although a larger sample size with longer follow-up is needed to compare this technique with others.